Analisis Tingkat Keterampilan Teknik Dasar Futsal pada Siswa Ekstrakulikuler Futsal SMA Negeri 2 Blora (Survei pada Peserta Ekstrakulikuler Futsal SMA Negeri 2 Blora) - Dhani, Dwiki Rachmad; Indarto, Pungki; Warthadi, Anugrah Nur (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aimed to determine the level of basic skills in playing futsal among students at SMA Negeri 2 Blora. The method used is a survey with test and measurement techniques. Objective data will be obtained through tests and measurements. The research subjects were extracurricular students at SMA Negeri 2 Blora, totaling 20 students. Data collection is carried out through observation and tests. Data analysis was carried out descriptively and quantitatively. The results of the research were that the level of futsal playing skills of futsal extracurricular students at SMA Negeri 2 Blora in 2024/2025 was declared